Factors of Satisfaction with Work–Life Balance: A Case of Freelancers - Irina Monakhova (Journal of Economic Sociology, 2016)
The present study focuses on an analysis of the factors in satisfaction with work–life balance in the case of Russian-language freelancers. The study is based on the demands-resources approach, which divides all factors of satisfaction with work–life balance into demands reducing the satisfaction and resources increasing it. The general purpose of the research is to study factors of satisfaction with work–life balance in terms of demands and resources among freelancers.The study is conducted in the context of a sequential strategy of biphasic mixed methods design with the following sequence of stages: preliminary qualitative input and quantitative research. The first task is to classify factors as belonging to demands or resources in work or family pheres on the basis of the literature review. The second task is to determine whether freelancers think in terms of demands and resources, or whether these categories are only abstract theoretical constructs. The third task is to examine the theoretical connection of factors to demands or resources.The list of factors in satisfaction with work–life balance, which contains factors, their theoretical and empirical descriptions (regression coefficients and qualitative interpretations), is presented as the final result of the study. It indicates not only the increase in the knowledge of factors in satisfaction with work–life balance but also the contribution to mixed methodology through description of the integration of quantitative and qualitative data.